Assessing the ecological components in the forestry related normal Environmental Impact Assessment (Eia) reports in Sabah - Sollyantianna Edward (2019)
Owing to an alarming commitment in environmental management, Environmental Impact Assessment (EIA) report has been used as a tool to identify, quantify and evaluate the potential impacts of defined actions towards the environment. As there exists data gap in the context of ecological components in the forestry related EIA reports in Sabah, this study intends to investigate the ecological component's inclusion and determine it's shortcomings in the selected EIA reports. Other than that, this study also aims to investigate whether three factors affect the quality of the ecological components in the forestry related Normal EIA, namely legth of EIA report; number of environmental consultants' E